Tetramic Acids Mutanocyclin and Reutericyclin A, Produced by Streptococcus mutans Strain B04Sm5 Modulate the Ecology of an in vitro Oral Biofilm - Uranga, Carla; Nelson, Karen E.; Edlund, Anna; Baker, Jonathon L. (Frontiers in Oral Health, 2022)
The human oral microbiome consists of diverse microbes actively communicating and interacting through a variety of biochemical mechanisms. Dental caries is a major public health issue caused by fermentable carbohydrate consumption that leads to dysbiosis of the oral microbiome. Streptococcus mutans is a known major contributor to caries pathogenesis, due to its exceptional ability to form biofilms in the presence of sucrose, as well as to its acidophilic lifestyle. S. mutans can also kill competing bacteria, which are typically health associated, through the production of bacteriocins and other small molecules. A subset of S. mutans strains encode the muc biosynthetic gene cluster (BGC), which was recently shown to produce the tetramic acids, mutanocyclin and reutericyclins A, B, and C. Reutericyclin A displayed strong antimicrobial activity and mutanocyclin appeared to be anti-inflammatory; however the effect of these compounds, and the carriage of muc by S. mutans, on the ecology of the oral microbiota is not known, and was examined here using a previously developed in vitro biofilm model derived from human saliva. While reutericyclin significantly inhibited in vitro biofilm formation and acid production at sub-nanomolar concentrations, mutanocyclin did not present any activity until the high micromolar range. 16S rRNA gene sequencing revealed that reutericyclin drastically altered the biofilm community composition, while mutanocyclin showed a more specific effect, reducing the relative abundance of cariogenic Limosilactobacillus fermentum. Mutanocyclin or reutericyclin produced by the S. mutans strains amended to the community did not appear to affect the community in the same way as the purified compounds, although the results were somewhat confounded by the differing growth rates of the S. mutans strains. Regardless of the strain added, the addition of S. mutans to the in vitro community significantly increased the abundance of S. mutans and Veillonella infantium, only. Overall, this study illustrates that reutericyclin A and mutanocyclin do impact the ecology of a complex in vitro oral biofilm; however, further research is needed to determine the extent to which the production of these compounds affects the virulence of S. mutans.